PENYELESAIAN MASALAH PROGRAM LINIER FUZZY DENGAN BILANGAN FUZZY MENGGUNAKAN METODE SABIHA LINEAR REAL - Eky Pawestri Gita Asmara (Jurnal Matematika, 2016)
ABSTRACT. Fuzzy Linear Programming (FLP) is one form of a linear programming that includes fuzzy numbers. Several methods have been developed to solve the FLP problems, one of which Sabiha’s Methods. The method is modifying Two Phase Methods such that it can be used in the FLP. Modification is done by changing the general form to be adjusted with the "triplet matrix", such that the one matrix of the triplet matrix is divided into three single matrix. The method is using Linear Fuzzy Real Numbers (LFR). There are also Kumar’s Methods were also modify Two Phase Methods. The comparison of the Sabiha’s Methods with Kumar’s Methods is resulting the same optimal solution and value in the form of fuzzy but there is a different in the form of crisp.